PENGGUNAAN INCLINED BITE PLANE SEBAGAI ALAT BANTU UNTUK KOREKSI GIGITAN SILANG ANTERIOR PADA KASUS MALOKLUSI KLAS III SKELETAL - Amutavia P. Artsianti P.; Erwin Siregar (Faculty of Dentistry, Universitas Indonesia, 2015)
Anterior crossbite occurs in children and adult. This anterior crossbite could be a dental (pseudo class III) or a skeletal class III malocclusions. A 15 year old young female came to orthodontic clinic RSGM FKGUI with maxillary dental crowding which canines were more protruded. The dental of mandible were more protruded than maxillary dental. The clinical examination, anamnesis, functional analyses and cephalometric evaluation and model study showed that it was a skeletal class III malocclusion with maxillary skeletal retrusion. To treat the anterior crossbite, the inclined bite plane is used for 2 weeks and followed by fixed appliance. After 2 month treatment, the anterior crossbite is resolved. The result of cephalometric evaluation showed that the use of inclined bite plane as a tool is quite effective to resolve this case.